Dor aguda : revisão do diagnóstico de enfermagem em pacientes com infarto agudo do miocárdio - Santos, Sônia Maria Josino dos (2014)
The objective of the study was the nursing diagnosis validation (ND) of Acute Pain of patient with Acute Myocardial Infarction (AMI). Methodological study developed in three stages of nursing diagnosis validation, found by the Hoskins model (1989): concept analysis, validation by specialists and clinical validation. In the first stage were Walker and Avant model (2005) and Whittemore; Knafl (2005) integrative review from the indexed journal search by the CINHAL, SCOPUS and PUBMED database access of studies published in the period between 2006 and 2012. The Pubmed and Cinahl database search used the indicated terminology, the MeSH – Medical Subject Headings of U.S National Library of Medicine English vocabulary. The Scopus database had DeCS – Descriptors Health Science structure vocabulary. To identify the different uses of acute concept, there was a study survey with the controlled descriptors Acute Pain and Myocardial Infarction in English language and Dolor Agudo and Infarto Miocardio in Spanish language. In the three databases search descriptor´s crossing we used the Boolean operator “AND”. “Acute pain” and “myocardial infarction” enlarge the crossing search. After applying the exclusion and inclusion criteria, 29 studies remained (from 535). There were four essential critical characteristics to understand acute pain concept. They are quality (constrictive, oppressive, pressure, tightness and weight, crushing feeling, typical ischemic, heartbreaking and grinding); location (retrosternal region, substernal, chest, the left side of the chest, sternum and through the center of the chest, right chest); time length (sudden onset, prolonged lasting 15 to 30 minutes, recurrent and intermittent); irradiation (neck, left shoulder, jaw, interscapular region, right and left arm, back, stomach, abdomen, epigastrium, left radial and brachial pulse). For the Acute Pain ND, NANDA-I presents 18 defined characteristics (DCs) identifying eight in the concept analysis adequate for Acute Pain diagnosis in AMI patients. Besides these ones, we found six more, in 15 DCs. There were elaboration of an instrument with the concept analysis definition, the constant NANDA-I and 14 DCs and their conceptual definitions and identified empiric references. Twenty-two specialists studied this instrument in nursing terminology and/or acute pain and/or acute myocardial infarction. From them (54,54%) they opted concept analysis definition. After appreciation, there were recommendation of the eight DCs identified in the NANDA-I and six new DCs for the ND Acute pain identified in the concept analysis. They were dyspnea; weakness; fatigue; nausea; Vomiting and paleness. The specialist tested in the clinical practice the 14 analyzed and validated DCs, through a transversal study done with 125 patients with AMI diagnosis. The findings showed that the acute pain, Diaphoresis, Fatigue, Paleness and Weakness are good indicators of the Acute Pain nursing diagnosis. The Elevated Blood Pressure, Sleep Disturbance, Elevated Heart Rate, Elevated Respiratory Rate, Dyspnea, Nausea, Vomiting, Anxiety and Fear DCs, were not satisfactory indicators of the study diagnosis. Therefore, five DCs were according to concept analysis, specialist validation and clinical validation, right to evaluate the Acute Pain ND in AMI patients.